Physicochemical characterization and metallurgical tests in the prospecting of polymetallic minerals in the Marañón-Peru Complex - Lovera, Daniel (2005)
Prospective studies developed in the zone of the Marañón basin show us a type of regional geology called the Marañón-Huánuco Region Complex, consisting of metallic minerals of Copper, Silver, Gold in schists and gneiss in contact with intrusives, as well as minerals of nickel, cobalt, titanium, platinum, among others. The characterization of the minerals in the area using instrumental techniques: minerographic microscope, Mössbauer spectroscopy analysis, multielemental chemical analysis, allow us to corroborate the presence of the metallic minerals of the Marañón Complex, as well as the presence of iron oxides, and to a degree of magnetization that are indicators of the metallic presence in the sampled areas. Metallurgical tests carried out indicate a good metallurgical recovery of the concentrates obtained for the chalcopyrite ore, which indicates a good economic possibility for the Marañón basin.